Blood transfusion in patients treated with surgery for necrotizing enterocolitis. Issue 2 (21st July 2014) - Ahmed, Zulfiqar; Danielson, Logan; Albeiruti, Rashad; Thomas, Ronald; Klein, Michael; Morton, Neil
Summary Background Necrotizing enterocolitis (NEC) is a common surgical emergency in premature infants and has high morbidity and mortality. Intraoperative treatment with fluid and transfusions may be difficult. Objectives We evaluated risk factors for patients who needed transfusion with packed red blood cells during surgery for necrotizing enterocolitis with bowel resection. Methods Retrospective medical and anesthetic record review of 206 patients who had necrotizing enterocolitis during 10 years at a pediatric referral center. Results In the 206 patients who had necrotizing enterocolitis, 88 patients (43%) had exploratory laparotomy, 67 with bowel resection. Of these, 50 needed transfusion of packed red blood cells in comparison with 17 who did not. Upon univariate analyses, patients who received packed red blood cells during surgery had significantly longer mean duration of surgery, lower preoperative hemoglobin and hematocrit, higher postoperative hemoglobin and hematocrit, more platelet transfusions, and greater estimated blood loss than patients who did not receive packed red blood cells during surgery. A binary logistic regression procedure revealed that the need for preoperative hemoglobin was found to be a significant risk factor for transfusion of packed red blood cells (odds ratio = 0.55; 95%CI = 0.36–0.84; P = 0.001). Conclusion Patients having necrotizing enterocolitis with bowel resection are more likely to need preoperative transfusion with packed red blood cells, which may be more necessary when surgery is longer, preoperative hematocrit is lower, and estimated blood loss is higher.